Estimation of Disaster Evacuation Shelter Capacity of Hitoyoshi City, Japan - Arbi Surya Satria Ridwan; Riken Homma; Hang Liu (Applied Research on Civil Engineering and Environment (ARCEE), 2022)
Heavy rains since early July 2020 have caused flooding in the Kyushu area. The Kuma River overflowed due to heavy rain. The river itself located in Kumamoto Prefecture right in the Hitoyoshi city. Disaster shelter is one of the most important requirements for those evacuated in the event of a disaster. It is used to analyze the supply and demand of the shelter based on the distance from the point of application to the disaster evacuation shelter, using the P-median model. As a result, the demand for evacuation shelters in the city of Hitoyoshi is 48%, which indicates that the demand for evacuation centers in case of disaster is about half. In this study, the location-allocation method was used in ArcGis 10.6 to determine the supply-demand ratio for Hitoyoshi. These data are expected to be used to optimize the operation of shelters in the Hitoyoshi area, an area prone to disasters for future urban development. This allows evacuation or disaster safety planners to develop tools for their area during floods and provides a way to predict when an event will occur and when roads will become unsafe for the residents during the future evacuation process. When a natural disaster happens again in the future, the demand and supply of disaster evacuation shelters should be assessed to determine their total capacity.